Ute land religion in the American West, 1879-2009 - Denison, Brandi (New visions in Native American and indigenous studies., 2017)
"A regional history of contact between Utes and white settlers, from 1879-2009, that examines the production of an idealized American religion in the American West through the intersection of religion, land, and cultural memory."--Provided by publisher